Formation à l’élaboration du rapport d’intervention : quelques réflexions sur la méthode pédagogique - Silvia Païn (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
After providing them with some theoretical references, training professionals in writing treatment reports can be better achieved by putting them in the position of the reader of the report instead of the writer. Such a change in perspective allows students to understand the communicative function of the report and improves significantly their writing abilities.